Sodium nitrite negatively affects reproductive ability and offspring survival in female mice. (1st November 2019) - Ge, Lei; Han, Zhe; Gao, Yu-Qing; Zhou, Cheng-Jie; Wang, Dong-Hui; Ma, Yu-Zhen; Liang, Cheng-Guang
Graphical abstract: Highlights: NaNO2 intragastric gavage deteriorates oocyte quality and reproductive ability. The deterioration in reproduction progresses in a dose dependent manner. NaNO2 mediated deterioration of reproduction is associated with ROS overproduction. Abstract: Sodium nitrite (NaNO2 ) is an industrial chemical that is frequently used as a food additive to prevent botulism and enhance glossiness, such as curing meat. In addition, in some regions, water source NaNO2 concentrations exceed standard regulatory levels. Whether the excessive intake of NaNO2 has toxic effects on female fertility and fetal development remain unknown. In this study, we administered ICR mice control saline, low-dose NaNO2 (60 mg/kg/day), or high-dose NaNO2 (120 mg/kg/day) by intragastric gavage for 21 days. We then assessed oocyte morphology, spindle-chromosome dynamics, mitochondrial distribution, ATP content, apoptotic cell numbers, DNA damage levels, histone modifications, reactive oxygen species (ROS) levels, and offspring survival. Results showed that NaNO2 treatment decreased oocyte number, impaired polar body extrusion, and increased zona pellucida thickness in oocytes. Furthermore, NaNO2 disrupted MII spindle integrity, caused abnormal mitochondrial distribution, decreased ATP content, and increased levels of ROS and H3K4me2. Moreover, the number of oocytes in early stages of apoptosis and with levels of DNA damage increased in NaNO2 -treated mice along with decreased offspring numbers and survival rates. We demonstrated the negative effects of NaNO2 on female reproductive abilities in mice.